Works Councils - Jens Mohrenweiser (Global Labor Organization (GLO), 2022)
This chapter reviews the economic effects of employee representation with statutory consultation and information rights at the workplace, the works councils. The chapter summarises the international literature which is heavily skewed towards the German case. This review focuses, first, on the mechanisms that enable the productivity enhancing role of works councils. Second, the review discusses the context factors that hamper or facilitate the productivity enhancing role of works councils. The chapter will start discussing the economic consequences of German works councils and then review the evidence obtained from other countries.
Keywords: J53; M54; J50; 330; works councils; codetermination; consultation; productivity; management practices